Engagement With Daily Testing Instead of Self-Isolating in Contacts of Confirmed Cases of SARS-CoV-2: A Qualitative Analysis - Sarah Denford; Sarah Denford; Sarah Denford; Alex F. Martin; Nicola Love; Derren Ready; Derren Ready; Isabel Oliver; Isabel Oliver; Richard Amlôt; Richard Amlôt; Richard Amlôt; et al. (Frontiers Media S.A., 2021)
Introduction: In December 2020 and January 2021 Public Health England (PHE) with NHS Test and Trace conducted a study to explore the feasibility and acceptability of daily testing as an alternative to self-isolation following close contact with a confirmed COVID-19 case. This qualitative paper aims to identify factors influencing uptake among those offered daily testing, and the subsequent impact on behaviour.Methods: We conducted in-depth interviews with 52 participants who had taken part in the feasibility study. Participants were asked about their experiences of daily testing or self-isolating, their reasons for choosing to test or isolate, and their behaviour during the study period. Data were analysed using inductive thematic analysis.Results: Results are presented under two main headings: (1) factors influencing acceptance of testing and (2) impact of test results. Participants appeared highly motivated to engage in behaviours that would protect others from the virus. Factors influencing the decision to accept testing included (1) needing to avoid self-isolation, (2) concerns about test sensitivity, and (3) perceived benefits of detecting infection. Participants who were taking tests reported: (1) positive consequences following confirmation of COVID status, (2) engaging in essential activities, (3) uncertainty, and (4) self-isolating whilst testing.Conclusions: This study has identified a range of factors that appear to influence the decision to engage in daily testing or to self-isolate following close contact with a positive case, many of which could be addressed by clear communications. Covid-19 infection rates and government restrictions influenced experiences, and so further research is needed to explore perceptions of daily testing and behaviour following close contact with a positive case among a wider range of individuals, in the context of lower rates of COVID-19, few government restrictions on general population behaviour and more widespread testing.